The moderating effects of CEO power and personal traits on say-on-pay effectiveness: Insights from the Anglo-Saxon economies - Joura, Essam; Xiao, Qin; Ullah, Subhan (International Journal of Finance and Economics, 2025)
This study investigates the efficacy of say-on-pay (SOP) regulation in mitigating excessive CEO compensation and how it is affected by CEO personal traits and the power distribution inside a corporation. Using IV-GMM method and a sample of 1,931 firms from Australia, Canada, the UK, and the USA, we find that shareholder voices are successful in reducing the pay gap between CEOs and the median employee, regardless of the exact nature of the regulation. In addition, older CEOs are associated with lower pay ratios and there are some evidences suggesting that older or female CEOs enhance SOP effectiveness. Further, power distribution manifested through corporate governance mechanisms matters, as increasing board size and director and audit committee independence reduce pay ratio. A measure of CEO power, CEO pay slice, has a significant and large positive explanatory power for the model and its exclusion can greatly exaggerate the estimated impact of SOP on pay ratio. Another measure of CEO power, CEO duality, appears to enhance the potency of SOP slightly. There is also some evidence indicating that ownership concentration enhances SOP effectiveness. Our findings have implications for companies, investors, and regulators concerning the importance of power balance structure within corporations.
Keywords: CEO pay; Executive compensation; IV-GMM; Pay ratio; Power distribution; Say-on-pay